A nano-silicon dioxide reinforced PP material and its preparation process

By adding nanosilicon dioxide and pretreated basalt fibers to the PP material, the problem of poor impact strength and tensile performance of PP material is solved, and the mechanical properties of the material are significantly improved and the application range is expanded.

CN119735890AInactive Publication Date: 2025-04-01LIUZHOU DASHENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411764464.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The impact strength and tensile properties of existing PP materials are poor, limiting their application range.

Method used

By adding nanosilicon dioxide and pretreated basalt fibers to the PP material, and using modified silica and composite fillers, the interface bonding and dispersion of the material are enhanced, and the mechanical properties of the material are improved.

Benefits of technology

The tensile strength, bending strength and impact strength of nano-silica-enhanced PP materials have been significantly improved, the wear resistance and fatigue resistance of the material have been improved, and its application range has been expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735890A_ABST
    Figure CN119735890A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-silicon dioxide reinforced PP material and a preparation process thereof, and the invention relates to the technical field of PP materials. The nano-silicon dioxide reinforced PP material is made of the following raw materials in parts by weight: 85-100 parts of polypropylene resin particles, 10-25 parts of composite fillers, 10-20 parts of basalt fibers, 1-3 parts of antioxidants, 15-20 parts of plasticizers, and 2-5 parts of reinforcing agents. The nano-silicon dioxide reinforced PP material and the preparation process thereof, by pre-treating the basalt fibers, make the surfaces thereof etched, micro-cracked, etc., become rougher, increase the contact area with the polypropylene matrix, thereby interlocking with the polypropylene, and enhancing the mechanical interlocking effect between the two; due to the enhancement of the interface bonding force, the basalt fibers can bear external forces more effectively, play a better supporting and reinforcing role in the polypropylene matrix, thereby improving the tensile strength of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PP materials, in particular to a nano-silicon dioxide reinforced PP material and a preparation process thereof. Background Art

[0002] Polypropylene is a thermoplastic resin made by polymerizing propylene. Methyl groups are arranged on the same side of the main chain of the molecule, which is called isotactic polypropylene. If the methyl groups are arranged disorderly on both sides of the main chain of the molecule, it is called atactic polypropylene. When the methyl groups are arranged alternately on both sides of the main chain of the molecule, it is called syndiotactic polypropylene. In the general industrially produced polypropylene resin, the isotactic structure content is about 95%, and the rest is atactic or syndiotactic polypropylene. Industrial products are mainly composed of isotactic substances. Polypropylene also includes copolymers of propylene and a small amount of ethylene. It is usually a translucent colorless solid, odorless and non-toxic. Due to its regular structure and high degree of crystallization, the melting point can be as high as 167°C. Heat resistance and corrosion resistance, and the products can be sterilized by steam are its outstanding advantages. It has a low density and is the lightest general-purpose plastic.

[0003] Nano silicon dioxide is one of the most important high-tech ultrafine inorganic new materials. It has very small particle size, large specific surface area, strong surface adsorption, large surface energy, high chemical purity, good dispersion performance, and special properties in thermal resistance and electrical resistance. With its superior stability, reinforcement, thickening and thixotropy, it has unique characteristics in many disciplines and fields and plays an irreplaceable role. Nano silicon dioxide, commonly known as "ultrafine white carbon black", is widely used in various industries as additives, catalyst carriers, petrochemicals, decolorizers, matting agents, rubber reinforcing agents, plastic fillers, ink thickeners, metal soft polishing agents, insulation and thermal insulation fillers, advanced daily cosmetics fillers and spray materials, medicine, environmental protection and other fields.

[0004] However, the impact strength and tensile properties of the PP materials currently on the market are relatively poor, which greatly limits the application scope of the PP materials. To this end, the present invention provides a nano-silicon dioxide reinforced PP material and a preparation process thereof to solve the above problems. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a nano-silicon dioxide reinforced PP material and a preparation process thereof, which solves the problems mentioned in the above background technology.

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a nano-silicon dioxide reinforced PP material, which is made of the following raw materials in parts by weight: 85-100 parts of polypropylene resin particles, 10-25 parts of composite fillers, 10-20 parts of basalt fibers, 1-3 parts of antioxidants, 15-20 parts of plasticizers, and 2-5 parts of reinforcing agents.

[0007] Preferably, the antioxidant is selected from any one of antioxidant 1010, antioxidant 264 and antioxidant 168; the plasticizer is maleic anhydride grafted polyethylene; and the reinforcing agent is white carbon black.

[0008] Preferably, the preparation method of the composite filler is:

[0009] S1. Pour 2-3.5 g of modified silica into 850-1000 mL of deionized water and disperse by ultrasonic for 45-60 min;

[0010] S2. Add 0.4-0.6 g of dopamine under stirring, and continue stirring at room temperature for 25-35 minutes;

[0011] S3, add 0.7-1.2 g of tris(hydroxymethyl)aminomethane, raise the temperature to 55-65°C, and continue stirring for 44-48 hours;

[0012] S4. After the reaction is completed, the product is centrifuged, washed with deionized water for 4-6 times, and then placed in a vacuum drying oven at 50-60° C. for 20-24 hours to obtain a composite filler.

[0013] Preferably, in S4, the centrifugal speed is 6000-8000 r / min, and the number of centrifugation times is 2-4 times.

[0014] Preferably, the preparation method of the modified silicon dioxide is:

[0015] Ⅰ. Pour 1-2.5 g of tetraoctylammonium bromide into 135-150 mL of xylene, stir for 15-20 min, add 3.5-5 g of silica, and ultrasonically treat for 45-60 min;

[0016] Ⅱ. Under nitrogen protection, slowly drop 0.6-1 mL of isocyanatepropyltriethoxysilane, raise the temperature to 75-80°C, and react for 22-24 hours;

[0017] III. After the reaction is completed, centrifuge, wash with xylene 3-4 times, grind and dry in a vacuum drying oven at 60-70°C for 10-12h to obtain modified silica.

[0018] A preparation process of nano-silicon dioxide reinforced PP material, specifically comprising the following preparation steps:

[0019] Step 1, weighing each raw material according to the weight ratio, and pre-treating the basalt fiber;

[0020] Step 2: Mix the polypropylene resin particles and the pretreated basalt fibers at a speed of 350-450 r / min for 8-10 min and a temperature of 108-112° C. to obtain a mixed material 1;

[0021] Step 3, adding antioxidant, plasticizer and reinforcing agent, and mixing at a speed of 600-700 r / min for 6-8 minutes to obtain mixed material 2;

[0022] Step 4, after mixing the mixture 1 and the mixture 2, add the composite filler, and mix at a speed of 650-750 r / min for 8-10 min to obtain the mixture 3;

[0023] Step 5: Pour the mixed material 3 into a twin-screw extruder for melting, and extrude and air-dry to form granules, wherein the temperature of each zone of the twin-screw extruder barrel is 180-185° C., and the screw speed is 40-45 r / min, to obtain nano-silicon dioxide reinforced PP material.

[0024] Preferably, in step 1, the specific method for pretreating the basalt fiber is: baking the basalt fiber at a temperature of 350-450° C. for 15-20 minutes, and then using an electron accelerator to irradiate the basalt fiber with electron beams in an air atmosphere.

[0025] Preferably, the irradiation dose is 100-200 kGy, and the irradiation time is 2-6 s.

[0026] Beneficial Effects

[0027] The present invention provides a nano-silicon dioxide reinforced PP material and a preparation process thereof. Compared with the prior art, it has the following beneficial effects:

[0028] (1) The nano-silicon dioxide reinforced PP material and its preparation process pre-treat basalt fibers to produce etching, micro-cracks, etc. on the surface of the basalt fibers, making the surface rougher and increasing the contact area with the polypropylene matrix, thereby interlocking with the polypropylene and enhancing the mechanical interlocking effect between the two. Due to the enhanced interface bonding force, the basalt fibers can more effectively bear external forces and play a better supporting and reinforcing role in the polypropylene matrix, thereby improving the tensile strength of the composite material. Moreover, the basalt fibers irradiated by electron beams can induce silver streaks and shear bands in the polypropylene, absorbing and dissipating more impact energy, making the composite material less likely to undergo brittle fracture when impacted, thereby improving its impact resistance.

[0029] (2) The nano-silica reinforced PP material and its preparation process modify silica to reduce the surface energy of silica particles, making them have better wettability in the organic phase, and at the same time making the silica particles more evenly dispersed in the polypropylene, reducing agglomeration, enhancing the interfacial bonding force between silica and the polypropylene matrix, effectively transmitting and dissipating external stress, preventing the expansion of cracks, and thus improving the toughness of the material; by adding composite fillers, the interfacial bonding force with polypropylene is further enhanced, thereby improving the toughness of the material, so that the composite material can more effectively transmit stress when subjected to force, thereby improving the mechanical properties of the material such as tensile strength, flexural strength and impact strength, and also improving the wear resistance and fatigue resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The SEM images of the silicon dioxide provided by the present invention before and after modification. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] A preparation process of nano-silicon dioxide reinforced PP material, specifically comprising the following preparation steps:

[0034] Step 1, weighing each raw material according to the weight ratio, and pre-treating 10g of basalt fiber: baking the basalt fiber at a temperature of 350°C for 15min, and then using an electron accelerator to irradiate the basalt fiber with an electron beam in an air atmosphere, with an irradiation dose of 100kGy and an irradiation time of 2s;

[0035] Step 2: 85 g of polypropylene resin particles and pretreated basalt fibers are mixed at a speed of 350 r / min and a temperature of 108° C. to obtain a mixed material 1;

[0036] Step 3, adding 1g of antioxidant 1010, 15g of maleic anhydride grafted polyethylene, and 2g of white carbon black, and mixing at a speed of 600r / min for 6min to obtain a mixture 2;

[0037] Step 4: Mix the mixture 1 and the mixture 2, add 10 g of the composite filler, and mix at a speed of 650 r / min for 8 min to obtain the mixture 3;

[0038] The preparation method of the composite filler is as follows: pour 1 g of tetraoctylammonium bromide into 135 mL of xylene, stir for 15 minutes, add 3.5 g of silica, and perform ultrasonic treatment for 45 minutes; slowly drop 0.6 mL of isocyanatepropyltriethoxysilane under nitrogen protection, heat to 75°C, and react for 22 hours; after the reaction is completed, centrifuge, wash with xylene 3 times, grind, and dry in a vacuum drying oven at 60°C for 10 hours to obtain modified silica;

[0039] 2 g of modified silica was poured into 850 mL of deionized water and ultrasonically dispersed for 45 min; 0.4 g of dopamine was added under stirring and continued to stir for 25 min at room temperature; 0.7 g of tris(hydroxymethyl)aminomethane was added, the temperature was raised to 55°C, and stirring was continued for 44 h; after the reaction was completed, the product was centrifuged twice at a speed of 6000 r / min, washed with deionized water 4 times, and then dried in a vacuum drying oven at 50°C for 20 h to obtain a composite filler;

[0040] Step 5: Pour the mixed material 3 into a twin-screw extruder for melting, and extrude and air-dry to form granules, wherein the temperature of each zone of the twin-screw extruder barrel is 180° C. and the screw speed is 40 r / min, thereby obtaining a nano-silicon dioxide reinforced PP material.

[0041] Example 2

[0042] A preparation process of nano-silicon dioxide reinforced PP material, specifically comprising the following preparation steps:

[0043] Step 1, weighing each raw material according to the weight ratio, and pre-treating 15g of basalt fiber: baking the basalt fiber at a temperature of 400°C for 18 minutes, and then using an electron accelerator to irradiate the basalt fiber with an electron beam in an air atmosphere, with an irradiation dose of 150kGy and an irradiation time of 4s;

[0044] Step 2: Mix 95 g of polypropylene resin particles and the pretreated basalt fibers at a speed of 400 r / min and a temperature of 110° C. to obtain a mixed material 1;

[0045] Step 3, adding 2 g of antioxidant 264, 18 g of maleic anhydride grafted polyethylene, and 3 g of white carbon black, and mixing at a speed of 650 r / min for 7 min to obtain a mixture 2;

[0046] Step 4: Mix the mixture 1 and the mixture 2, add 15 g of the composite filler, and mix at a speed of 700 r / min for 9 minutes to obtain a mixture 3;

[0047] The preparation method of the composite filler is as follows: pour 1.5 g of tetraoctylammonium bromide into 140 mL of xylene, stir for 18 minutes, add 4.5 g of silica, and perform ultrasonic treatment for 55 minutes; slowly drop 0.8 mL of isocyanatepropyltriethoxysilane under nitrogen protection, heat to 78°C, and react for 23 hours; after the reaction is completed, centrifuge, wash with xylene 4 times, grind, and dry in a vacuum oven at 65°C for 11 hours to obtain modified silica;

[0048] 2.5 g of modified silica was poured into 900 mL of deionized water and ultrasonically dispersed for 50 min; 0.5 g of dopamine was added under stirring and continued to stir at room temperature for 30 min; 0.9 g of tris(hydroxymethyl)aminomethane was added, the temperature was raised to 60°C, and stirring was continued for 46 h; after the reaction was completed, the product was centrifuged at a speed of 7000 r / min for 3 times, washed with deionized water for 5 times, and then placed in a vacuum drying oven at 55°C for 22 h to obtain a composite filler;

[0049] Step 5: Pour the mixed material 3 into a twin-screw extruder for melting, and extrude and air-dry to form granules, wherein the temperature of each zone of the twin-screw extruder barrel is 183° C., and the screw speed is 42 r / min, to obtain the nano-silicon dioxide reinforced PP material.

[0050] Example 3

[0051] A preparation process of nano-silicon dioxide reinforced PP material, specifically comprising the following preparation steps:

[0052] Step 1, weighing each raw material according to the weight ratio, and pre-treating 20g of basalt fiber: baking the basalt fiber at a temperature of 450°C for 20min, and then using an electron accelerator to irradiate the basalt fiber with an electron beam in an air atmosphere, with an irradiation dose of 200kGy and an irradiation time of 6s;

[0053] Step 2: 100 g of polypropylene resin particles and pretreated basalt fibers are mixed at a speed of 450 r / min and a temperature of 112° C. to obtain a mixed material 1;

[0054] Step 3, adding 3 g of antioxidant 168, 20 g of maleic anhydride grafted polyethylene, and 5 g of white carbon black, and mixing at a speed of 700 r / min for 8 min to obtain a mixture 2;

[0055] Step 4: Mix the mixture 1 and the mixture 2, add 25 g of the composite filler, and mix at a speed of 750 r / min for 10 min to obtain the mixture 3;

[0056] The preparation method of the composite filler is as follows: pour 2.5 g of tetraoctylammonium bromide into 150 mL of xylene, stir for 20 min, add 5 g of silica, and perform ultrasonic treatment for 60 min; slowly drop 1 mL of isocyanatepropyltriethoxysilane under nitrogen protection, heat to 80°C, and react for 24 h; after the reaction is completed, centrifuge, wash with xylene 4 times, grind, and dry in a vacuum drying oven at 70°C for 12 h to obtain modified silica;

[0057] 3.5 g of modified silica was poured into 1000 mL of deionized water and ultrasonically dispersed for 60 min; 0.6 g of dopamine was added under stirring and continued to stir at room temperature for 35 min; 1.2 g of tris(hydroxymethyl)aminomethane was added, the temperature was raised to 65°C, and stirring was continued for 48 h; after the reaction was completed, the product was centrifuged 4 times at a speed of 8000 r / min, washed 6 times with deionized water, and then placed in a vacuum drying oven at 60°C for 24 h to obtain a composite filler;

[0058] Step 5: Pour the mixed material 3 into a twin-screw extruder for melting, and extrude and air-dry to form granules, wherein the temperature of each zone of the twin-screw extruder barrel is 185° C. and the screw speed is 45 r / min, thereby obtaining a nano-silicon dioxide reinforced PP material.

[0059] Comparative Example 1

[0060] Compared with Example 1, the difference is that the basalt fiber is not pretreated.

[0061] Comparative Example 2

[0062] Compared with Example 1, the difference is that the modified silica in the composite filler of Example 1 is replaced by silica.

[0063] Comparative Example 3

[0064] Compared with Example 1, the difference is that the composite filler in Example 1 is replaced by modified silica.

[0065] Impact performance test: Tested in accordance with GB / T1447-2005.

[0066] Tensile performance test: Tested in accordance with GB / T1040.2-2006.

[0067] Bending performance test: Tested in accordance with GB / T9341-2008.

[0068] <![CDATA[Impact strength (KJ / m 2 )]]> Tensile strength(MPa) Bending strength(MPa) Example 1 32.15 36.52 51.49 Example 2 32.08 36.25 50.96 Example 3 31.94 35.48 50.27 Comparative Example 1 25.16 30.08 42.16 Comparative Example 2 26.83 31.84 44.07 Comparative Example 3 23.97 28.69 39.82

[0069] like Figure 1As shown, before modification, the silica aggregates together and agglomerates; after modification, a rough and dense coating is attached to the surface of the silica, which can effectively reduce the interaction force between silicas and improve their dispersibility.

[0070] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0071] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nano-silicon dioxide reinforced PP material, characterized in that: The nano silicon dioxide reinforced PP material is made of the following raw materials in parts by weight: 85-100 parts of polypropylene resin particles, 10-25 parts of composite fillers, 10-20 parts of basalt fibers, 1-3 parts of antioxidants, 15-20 parts of plasticizers, and 2-5 parts of reinforcing agents.

2. The preparation process of a nano-silicon dioxide reinforced PP material according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 264 and antioxidant 168; the plasticizer is maleic anhydride grafted polyethylene; and the reinforcing agent is white carbon black.

3. The nano-silicon dioxide reinforced PP material according to claim 1, characterized in that: The preparation method of the composite filler is: S1. Pour 2-3.5 g of modified silica into 850-1000 mL of deionized water and disperse by ultrasonic for 45-60 min; S2. Add 0.4-0.6 g of dopamine under stirring, and continue stirring at room temperature for 25-35 minutes; S3, add 0.7-1.2 g of tris(hydroxymethyl)aminomethane, raise the temperature to 55-65°C, and continue stirring for 44-48 hours; S4. After the reaction is completed, the product is centrifuged, washed with deionized water for 4-6 times, and then placed in a vacuum drying oven at 50-60° C. for 20-24 hours to obtain a composite filler.

4. The nano-silicon dioxide reinforced PP material according to claim 3, characterized in that: In S4, the centrifugal speed is 6000-8000 r / min, and the number of centrifugation is 2-4 times.

5. The nano-silicon dioxide reinforced PP material according to claim 3, characterized in that: The preparation method of the modified silicon dioxide is: Ⅰ. Pour 1-2.5 g of tetraoctylammonium bromide into 135-150 mL of xylene, stir for 15-20 min, add 3.5-5 g of silica, and ultrasonically treat for 45-60 min; Ⅱ. Under nitrogen protection, slowly drop 0.6-1 mL of isocyanatepropyltriethoxysilane, raise the temperature to 75-80°C, and react for 22-24 hours; III. After the reaction is completed, centrifuge, wash with xylene 3-4 times, grind and dry in a vacuum drying oven at 60-70°C for 10-12h to obtain modified silica.

6. A process for preparing nano-silicon dioxide reinforced PP material according to claim 1, characterized in that: The specific preparation steps include: Step 1, weighing each raw material according to the weight ratio, and pre-treating the basalt fiber; Step 2: Mix the polypropylene resin particles and the pretreated basalt fibers at a speed of 350-450 r / min for 8-10 min and a temperature of 108-112° C. to obtain a mixed material 1; Step 3, adding antioxidant, plasticizer and reinforcing agent, and mixing at a speed of 600-700 r / min for 6-8 minutes to obtain mixed material 2; Step 4, after mixing the mixture 1 and the mixture 2, add the composite filler, and mix at a speed of 650-750 r / min for 8-10 min to obtain the mixture 3; Step 5: Pour the mixed material 3 into a twin-screw extruder for melting, and extrude and air-dry to form granules, wherein the temperature of each zone of the twin-screw extruder barrel is 180-185° C., and the screw speed is 40-45 r / min, to obtain nano-silicon dioxide reinforced PP material.

7. The preparation process of a nano-silicon dioxide reinforced PP material according to claim 6, characterized in that: In the step 1, the specific method for pre-treating the basalt fiber is: baking the basalt fiber at a temperature of 350-450° C. for 15-20 minutes, and then using an electron accelerator to irradiate the basalt fiber with electron beams in an air atmosphere.

8. The process for preparing a nano-silicon dioxide reinforced PP material according to claim 7, characterized in that: The irradiation dose is 100-200 kGy, and the irradiation time is 2-6 s.